History, Infanticide, and Imperiled Newborns - Post, Stephen G. (The Hastings Center report, 1988)
Ethicists who advocate the permissibility of infanticide often have misrepresented history in their arguments. The Western tradition supports the prohibition of active killing of congenitally impaired or premature newborns whose futures are uncertain.